Psychometric properties of an adapted working alliance scale among Latinos - Cartujano-Barrera, Francisco; Cupertino, Alessandra Fabrino Bretas; Lara, Daimarelys; Sartes, Laisa Marcorela Andreoli; Ramos-Santiago, Jeffrey W.; Torres, Ciara A.; Ponce, Dora; Catley, Delwyn; Cox, Lisa Sanderson; Cupertino, Ana Paula (Frontiers in Psychology, 2026)
ObjectiveTo assess the psychometric properties (i.e., internal consistency reliability, factorial validity, concurrent validity, and discriminant validity) of the Working Alliance with Smoking Cessation Program (WASCOP) Scale, an adapted scale of working alliance designed for “non-traditional” therapeutic settings.MethodsThis was a secondary data analysis of the Month 3 follow-up data from Decídetexto, a randomized clinical trial assessing the efficacy of a culturally accommodated mobile smoking cessation intervention among Latinos. The sample included 374 participants who completed at least 10 of the 12 WASCOP items. Analyses included Cronbach’s alpha, exploratory factor analysis, and Spearman’s correlations with study satisfaction and smoking self-efficacy.ResultsFollowing the removal of two negatively worded items, the 10-item WASCOP Scale demonstrated excellent internal consistency (α = 0.91). Factor analysis supported a two-factor structure. WASCOP scores were moderately correlated with program satisfaction (r = 0.530) and weakly with self-efficacy (r = 0.318), supporting construct and discriminant validity.ConclusionThe 10-item WASCOP Scale possesses acceptable internal consistency reliability, construct validity, and concurrent validity among Latinos. These findings support it potential applications in both research and clinical settings.